2021
DOI: 10.1007/s11259-021-09854-8
|View full text |Cite
|
Sign up to set email alerts
|

Diet and dog characteristics affect major and trace elements in hair and blood of healthy dogs

Abstract: Obtaining correct amounts of essential elements, and avoiding toxic metals are key factors in dog health. Through analyzing major and trace elements in hair and blood of 50 healthy companion dogs using ICP-MS, we study their associations with dog characteristics and diet, hypothesizing that eating the same diet long-term results in strong correlations between hair and blood element concentrations, and that dog characteristics and diet affect element status. The correlation between hair and blood was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 83 publications
(118 reference statements)
1
14
5
Order By: Relevance
“…Unfortunately, reference values for blood Cu in dogs have not been established. However, the mean blood Se concentration of the epileptic dogs in the current study (511.95 ng/g) was higher than that reported in our previous study on 50 healthy dogs (483.79 ng/g) ( 25 ) and in another study by Panda et al ( 30 ) (480 ng/g), although none of the epileptic dogs had Cu concentrations that were outside the range that were reported in these two studies. Our study also found that the Cu/Zn ratio, which in humans has been regarded as clinically more important than the concentrations of Cu or Zn alone ( 31 ), was significantly higher in epileptic compared to healthy dogs, which is consistent with what has been reported in serum of children with idiopathic seizures ( 28 ).…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Unfortunately, reference values for blood Cu in dogs have not been established. However, the mean blood Se concentration of the epileptic dogs in the current study (511.95 ng/g) was higher than that reported in our previous study on 50 healthy dogs (483.79 ng/g) ( 25 ) and in another study by Panda et al ( 30 ) (480 ng/g), although none of the epileptic dogs had Cu concentrations that were outside the range that were reported in these two studies. Our study also found that the Cu/Zn ratio, which in humans has been regarded as clinically more important than the concentrations of Cu or Zn alone ( 31 ), was significantly higher in epileptic compared to healthy dogs, which is consistent with what has been reported in serum of children with idiopathic seizures ( 28 ).…”
Section: Discussioncontrasting
confidence: 86%
“…However, the mean blood Se concentration in epileptic dogs in the current study (488.53 ng/g) is clearly higher than that reported in our previous study on 50 clinically healthy dogs (388.14 ng/g). Twelve out of the 19 epileptic dogs also had blood Se concentrations that were higher than the maximum concentration reported in that study ( 25 ). As dogs commonly eat commercial diets with added Se, they are very unlikely to become deficient.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Thus, the mineral content of dog food needs to be frequently monitored 5 . Long-term use of the same diet results in correlations between the concentrations of the elements in the blood and in the hair coat 6 . Dark hair contains more Ca and Mg compared to fair hair.…”
Section: Introductionmentioning
confidence: 99%